Starost kot varovalni dejavnik kognitivne okvare po pridobljeni možganski poškodbi - Čižman Štaba, Urša (Rehabilitacija (Ljubljana), 2019)
Introduction: We examined whether younger during acquired brain injury (ABI) protects against acquired cognitive impairment. Methods: The profile of cognitive improvement over time after ABI was assessed for a group of children and adolescents, for whom the effects of cognitive rehabilitation were compared to those of a group of adults. The current pilot study included 25 participants (14 children/adolescents and 11 adults). A neuropsychological battery was used to assess cognitive functioning at two time points (T1 % six months, and T2 % 12 months after ABI). The neuropsychological battery entailed the assessment of attention processing, verbal memory functions, executive functions and mental processing speed. Results: The results showed a statistically significant effect of cognitive rehabilitation over time, whereby mental speed processing improved for both groups; additionally, we observed statistically significant improvement of executive functions in the group of adults. When comparing the groups, the results show statistically significantly better cognitive functioning in the group of children and adolescents, who attained higher scores on divided attention at six months (T1) but not at 12 months after ABI (T2), as well as on memory functioning, where they attained statistically significantly better results at both time points (T1 and T2) for recall and delayed recall of verbal material. The effect of cognitive rehabilitation was similar in both groups; however, statistically significant improvement on several cognitive areas was detected within the group of adolescents. Conclusion: The protective effect of younger age for cognitive functioning after the ABI was confirmed for verbal memory at both time points.
Keywords: acquired brain injury; age; Brain Injuries; Cognition; cognitive functioning; kognitivne sposobnosti; memory; neuropsychology; nevropsihologija; pridobljena možganska poškodba; rehabilitation; spomin; starost